Romanian Words and Set Expressions Designating Pies - Savin, Petronela (Acta Universitatis Danubius. Communicatio, 2024)
The aim of this paper is to approach the Romanian culinary terminology by assuming the gains from the space of nowadays’ linguistics, in an attempt to respond to the challenge formulated by Eugenio Coseriu regarding the study of language as a creative activity that justifies linguistics as a science of culture. Food knowledge discourses are an extremely important source of documentation for explaining the mechanisms of linguistic creation. The way Romanian terms and expressions related to pies are formed and function is a relevant example to illustrate the relationship between the act of naming and its path to figurativeness.